The effect of negative automatic thoughts on hope in patients with schizophrenia - Budak, Funda Kavak; Yildirim, Tulay; Ozdemir, Aysel (Wiley, 2021)
Purpose The purpose of this study is to determine the effect of negative automatic thoughts on hope in patients with schizophrenia. Design and Methods The sample size of the study was calculated to be 94 patients through the power analysis. The study was completed with 115 patients who met the inclusion criteria. descriptive characteristics form, automatic thoughts questionnaire-negative, and dispositional hope scale were used to collect the data. Findings In the study, it was found that there was a negative strong correlation between negative automatic thoughts and hope levels. In addition, the negative automatic thoughts of the patients had a statistical significance in accounting for hope (p < .05) and the negative automatic thoughts predicted the hope by 66%. Practice Implications In the study, it was found that the patients had high negative automatic thoughts and moderate level of hopes. As negative automatic thoughts increased, hope decreased.
Keywords: hope; negative automatic thought; patient; schizophrenia